2019
DOI: 10.1029/2018wr023629
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for Model Uncertainty Quantification: A Hybrid Ensemble and Variational Data Assimilation Framework

Abstract: This article presents a novel approach to couple a deterministic four‐dimensional variational (4DVAR) assimilation method with the particle filter (PF) ensemble data assimilation system, to produce a robust approach for dual‐state‐parameter estimation. In our proposed method, the Hybrid Ensemble and Variational Data Assimilation framework for Environmental systems (HEAVEN), we characterize the model structural uncertainty in addition to model parameter and input uncertainties. The sequential PF is formulated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 76 publications
(101 reference statements)
0
55
0
Order By: Relevance
“…Abbaszadeh et al. (2019) suggest using the 4D‐variational method for this initial state optimization, but for the case of hydraulic models developing the adjoint model is a major scientific challenge. Moreover, selecting among several well‐performing models is incredibly difficult using binary flood extents.…”
Section: Methodsmentioning
confidence: 99%
“…Abbaszadeh et al. (2019) suggest using the 4D‐variational method for this initial state optimization, but for the case of hydraulic models developing the adjoint model is a major scientific challenge. Moreover, selecting among several well‐performing models is incredibly difficult using binary flood extents.…”
Section: Methodsmentioning
confidence: 99%
“…The flash flood events that caused property damage were randomly divided into two parts: training (85% of dataset) and testing (15% dataset). The result of the developed model are evaluated using two performance measures: correlation coefficient (R) and bias, both of which have been commonly used to measure the accuracy and performance of the ML models (Gavahi et al 2019, Neri et al 2019, Shastry and Durand 2019, Abbaszadeh et al 2019a. Here, the regression (i.e.…”
Section: Damage Prediction Modelmentioning
confidence: 99%
“…Although very promising results have been achieved, the procedure of model linearization can be complicated for strongly nonlinear dynamic system. There are also other studies showed that the gradient‐based inverse modeling can be implemented without calculating the adjoint and tangent linear model when they are integrated with ensemble‐based data assimilation approaches (Abbaszadeh et al., 2019; Hernández & Liang, 2018).…”
Section: Introductionmentioning
confidence: 99%